2018
DOI: 10.3390/v10090472
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Potential Virulence Factors and RNA Silencing Suppressors of Mulberry Mosaic Dwarf-Associated Geminivirus

Abstract: Plant viruses encode virulence factors or RNA silencing suppressors to reprogram plant cellular processes or to fine-tune host RNA silencing-mediated defense responses. In a previous study, Mulberry mosaic dwarf-associated virus (MMDaV), a novel, highly divergent geminivirus, has been identified from a Chinese mulberry tree showing mosaic and dwarfing symptoms, but the functions of its encoded proteins are unknown. In this study, all seven proteins encoded by MMDaV were screened for potential virulence and RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 59 publications
4
38
1
Order By: Relevance
“…At 14 dpi, the PVX-C1-inoculated plants showed severe dwarfing symptoms (the overlapped C4 gene in the C1 gene has been mutated, so the symptom is caused only by the C1 protein). Previous research also showed that the C1 protein of Mulberry mosaic dwarf-associated virus can cause similar symptoms in host plants (Yang et al, 2018). Furthermore, Wezel et al found that PVX-driven expression of C1+C4 causes local and systemic necrosis in N. benthamiana, and that C4 is necessary for systemic necrosis induction (using a C1 mC4 construct) (Wezel et al, 2002).…”
Section: Discussionmentioning
confidence: 94%
“…At 14 dpi, the PVX-C1-inoculated plants showed severe dwarfing symptoms (the overlapped C4 gene in the C1 gene has been mutated, so the symptom is caused only by the C1 protein). Previous research also showed that the C1 protein of Mulberry mosaic dwarf-associated virus can cause similar symptoms in host plants (Yang et al, 2018). Furthermore, Wezel et al found that PVX-driven expression of C1+C4 causes local and systemic necrosis in N. benthamiana, and that C4 is necessary for systemic necrosis induction (using a C1 mC4 construct) (Wezel et al, 2002).…”
Section: Discussionmentioning
confidence: 94%
“…In African cassava mosaic virus (ACMV), the suppressor of silencing is C4 like Tomato leaf curl New Delhi virus (ToLCNDV) [26,59], while in CLCuDV both TrAP and C4 have suppressor functions [24]. Another protein associated with suppression is V2 from Mulberry mosaic dwarf-associated virus (MMDAV), Apple geminivirus (AGV), Tomato yellow leaf curl virus (TYLCV), and Beet curly top virus (BCTV) [29,48,[60][61][62]. Therefore, despite belonging to the same viral family each virus has different suppressor silencing proteins, so this function cannot be generalized in all geminiviruses and it is necessary to analyze each individual virus.…”
Section: Discussionmentioning
confidence: 99%
“…The RepA, V2, and V3 genes from MMDaV (GenBank accession number KP303687) (Ma et al, 2015), the V2 dm61−77aa from pGEM-T-V2 dm61−77aa (Yang et al, 2018) and the coding sequences of the fibrillarin 2 gene of N. benthamiana cDNA (GenBank accession number AM269909, NbFib2) were cloned into pENTR-D/TOPO entry vector without stop codon by standard protocols (Invitrogen, Beijing, China) to yield pENTR-RepA, pENTR-V2, pENTR-V3, pENTR-V2 dm61−77aa , and pENTR-NbFib2, respectively. For subcellular localization analysis, NbFib2 and RepA was gateway-cloned into plant binary vectors pEarleyGate102 [N-terminal cyan fluorescent protein (CFP) fusion] and pGWB454 (N-terminal RFP fusion) to yield Fib2-RFP and RepA-CFP, respectively (Earley et al, 2006;Nakagawa et al, 2007).…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…Grapevine red blotch-associated virus (GRBaV) V2 localizes to the nucleoplasm, Cajal bodies, and cytoplasm, and is redirected to the nucleolus upon coexpression with the nucleus and Cajal body-associated protein fibrillarin 2 (Fib2) (Guo et al, 2015). The V2 protein of a distinct monopartite geminivirus, Mulberry mosaic dwarf-associated virus (MMDaV), was shown to localize to both subnuclear foci and cytoplasm of the epidermal cells of Nicotiana benthamiana plants (Yang et al, 2018). Most of these experiments, however, have studied the subcellular localization of V2 in the absence of virus infection.…”
Section: Introductionmentioning
confidence: 99%